Effects of Climate-Related Financial Risk on Foreign Direct Investment and Economic Stability in Developing Countries - Fricy Rumintjap; Eko Sudarmanto; Arvy N. Osma (International Forum of Researchers and Lecturers, 2024)
Climate change is increasingly recognized as a significant financial risk factor, particularly in developing countries where financial systems are often less resilient to environmental shocks. This study explores the relationship between climate-related financial risks, Foreign Direct Investment (FDI), and economic stability in developing nations. It highlights how both physical risks, such as extreme weather events (e.g., floods and droughts), and transition risks, including regulatory changes and shifts toward a low-carbon economy, deter FDI and contribute to economic volatility. The findings show that developing countries, which are more vulnerable to these risks, experience reduced FDI inflows due to the increased costs of adaptation and the potential for operational disruptions. Additionally, the study finds that countries with weaker financial institutions and governance structures are more susceptible to the economic instability induced by climate risks. The analysis suggests that climate risk mitigation strategies, such as strengthening financial sectors, improving governance, and implementing effective climate policies, can help reduce these risks and create a more stable investment environment. The research also identifies gaps in the literature, particularly the combined effect of climate risks and financial instability on FDI, which warrants further exploration. The study calls for more comprehensive research, particularly focusing on regional case studies and sector-specific impacts, to guide policymakers in fostering a climate-resilient economic environment that attracts sustainable foreign investment.